2015
DOI: 10.1016/j.egypro.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Plasma-based Technologies

Abstract: This study presents a comprehensive analysis of costs and benefits of technologies based on cold plasma for the removal of sulfur and nitrogen oxides of flue gases. Assessment is based on welfare economics and seeks to include all relevant costs and benefits to evaluate the net social benefit of a project. A plasma unit installed in a CHP plant was used as the case study for this study. Results obtained from the study showed that the use of plasma technology is not financially viable unless all economic, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Although plasma assisted techniques for the flue gas treatment have shown good progress, yet the industrial applicability of plasma-based techniques is questionable. 30 Another recent study conducted by Zhao et al, 31 showed deNOx effect using Ce-modified Cu-BTC catalysts in presence of CO at low temperature by in situ DRIFTS. The results demonstrated that the adsorption modes of NO on the catalysts form the following species; monodentate nitrites, chelating bidentate nitrates, bridging bidentate nitrates, trans-N 2 O 2 2and NOspecies (Scheme S1), whereas the adsorption forms of CO form hydrogen carbonate, carbonate and carbonyl species (Scheme S2).…”
Section: R a F Tmentioning
confidence: 98%
“…Although plasma assisted techniques for the flue gas treatment have shown good progress, yet the industrial applicability of plasma-based techniques is questionable. 30 Another recent study conducted by Zhao et al, 31 showed deNOx effect using Ce-modified Cu-BTC catalysts in presence of CO at low temperature by in situ DRIFTS. The results demonstrated that the adsorption modes of NO on the catalysts form the following species; monodentate nitrites, chelating bidentate nitrates, bridging bidentate nitrates, trans-N 2 O 2 2and NOspecies (Scheme S1), whereas the adsorption forms of CO form hydrogen carbonate, carbonate and carbonyl species (Scheme S2).…”
Section: R a F Tmentioning
confidence: 98%
“…27 Energy efficiency is important to lower operational costs and improve carbon footprints, whereas capital expenditures matter for assessing the affordability of units. Estimated energy and capital cost requirements of existing PFAS destruction techniques, based on literature data, 167,[229][230][231][232][233][234][235][236][237] are shown in Fig. 4.…”
Section: Globally Scalable Viable Technologies Must Work In Aqueous M...mentioning
confidence: 99%
“…238 The equivalent electrical energy requirement to achieve 90% sulfadiazine degradation by g-irradiation from a 60 Co source, taken here as a proxy for PFAS degradation, at a constant dose rate of 6.69 kGy h À1 has been reported to be 18 kW h m À3 . 239 The capital investment for non-thermal plasma 231,237 of $92 329 was obtained from a capital cost approximation for industrial wastewater plants. 163,240 The energy required to achieve a high removal rate of PFOA from water using non-thermal plasma is 100 kW h m À3 , which was deduced from the energy efficiency of non-thermal plasma setups.…”
Section: Chemcomm Highlightmentioning
confidence: 99%
“…SD modelēšana Latvijā ir lietota vairākās publikācijās, piem., RTU zinātnieki ir izstrādājuši ne-ETS enerģētiskās sistēmas SD modeli 48 , kas izmantots dažādu ekonomisko metožu analīzei pārejai uz atjaunojamiem energoresursiem 49 , kā arī pārejai uz modernām siltuma sistēmām 50 .…”
Section: Modelēšanas Metožu Pielietojums Latvijāunclassified